2012
DOI: 10.1007/s11356-012-1395-x
|View full text |Cite
|
Sign up to set email alerts
|

The response of mulberry trees after seedling hardening to summer drought in the hydro-fluctuation belt of Three Gorges Reservoir Areas

Abstract: Interest has developed in the potential of mulberry (Morus alba), a woody perennial, for revegetating the hydro-fluctuation belt of the Three Gorges Reservoir due to its resistance to water-logging stress. To be useful, the trees must also be able to withstand dry conditions in summer when temperatures can be very high and droughts become severe quickly. Here, we report a study in which mulberry seedlings were grown in a greenhouse under a variety of simulated soil water conditions reflecting potential summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…In order to reduce the adverse impact of drought stress on crop production, several methods and technologies have been put to use to enhance the drought resistance of crops. Drought hardening is a convenient and feasible method and involves exposing plants to arid conditions such as reduced irrigation or partial drought during the seedling stage so as to improve the ability to adapt to subsequent serious drought (Thomas 2009;Huang et al 2013). The effectiveness of drought hardening lies in the fact that young plants are malleable and are usually more able to survive under arid conditions if they have undergone a previous period of low moisture stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the adverse impact of drought stress on crop production, several methods and technologies have been put to use to enhance the drought resistance of crops. Drought hardening is a convenient and feasible method and involves exposing plants to arid conditions such as reduced irrigation or partial drought during the seedling stage so as to improve the ability to adapt to subsequent serious drought (Thomas 2009;Huang et al 2013). The effectiveness of drought hardening lies in the fact that young plants are malleable and are usually more able to survive under arid conditions if they have undergone a previous period of low moisture stress.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that drought hardening applied in the nursery before planting improved the seedling survival rate under extreme xeric conditions (Driessche 1991). In addition, seedling hardening can improve the growth adaptability and drought resistance of mulberry (Huang et al 2013). This strategy has been widely adopted in wheat, rice and other plants.…”
Section: Introductionmentioning
confidence: 99%
“…The root length reduction may be attributed to lower cellular division and elongation during germination [47]. The root/shoot ratio is an important index for measuring the development of seedling roots, and plants with higher root/shoot ratios are more capable of absorbing water and minerals [48].…”
Section: Resultsmentioning
confidence: 99%
“…The ranges of tolerance related to these variables are not yet known. M. alba is a riparian species that is known to tolerate physiological stresses such as freezing, drought and water-logging [15], [19], [20], but it was not expected to survive the severe stress of long-term winter flooding to depths that cover the crown of the tree. Following observation of mulberry survival, new experimental plantations have been established recently in the TGR drawdown zone in Yunyang and Wanzhou (regions of Chongqing) and some young transplanted trees have survived for up to four annual cycles at submersion depths up to 7m (authors' personal observations of unreported experiments).…”
Section: Plant Stressmentioning
confidence: 99%